2021
DOI: 10.3390/coatings11020227
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Zr Alloy under High-Temperature Air Oxidation: A Multilayer Coating Approach

Abstract: Metallic Cr and multilayer CrN/Cr coatings with a thickness of 2.5 µm were deposited onto E110 alloy by magnetron sputtering. Oxidation tests in air were performed at 1100 °C for 10–40 min. The gravimetric measurements showed better protective properties of multilayer CrN/Cr coatings in comparison with metallic Cr coating. Multilayer coating prevented fast Cr–Zr inter-diffusion by the formation of a ZrN layer beneath the coating. The appearance of ZrN is caused by interaction with nitrogen formed from the deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…For materials used in the sustainable energy domain, investigations of properties are continuous, to enhance selection [1]. In the nuclear field, the corrosion processes of all metallic materials have determining roles in efficiently and safely operating a nuclear power plant (NPP), and their oxidation processes are largely investigated as functions of the environment for their industrial exploitation [2][3][4][5]. Zirconium-based alloys serve the nuclear industry as metallic tubes called cladding, where the nuclear fuel element is located and assembled.…”
Section: Introductionmentioning
confidence: 99%
“…For materials used in the sustainable energy domain, investigations of properties are continuous, to enhance selection [1]. In the nuclear field, the corrosion processes of all metallic materials have determining roles in efficiently and safely operating a nuclear power plant (NPP), and their oxidation processes are largely investigated as functions of the environment for their industrial exploitation [2][3][4][5]. Zirconium-based alloys serve the nuclear industry as metallic tubes called cladding, where the nuclear fuel element is located and assembled.…”
Section: Introductionmentioning
confidence: 99%
“…Sidelev et al demonstrated the barrier properties of multilayer CrN/Cr (250/250 nm) coatings against Cr-Zr inter-diffusion during heating up to 1400 • C (Figure 16) [195]. It was found that the diffusion limitation was attributed not only to CrN layers but also to a ZrN layer formed beneath the multilayers due to the decomposition of chromium nitrides at high temperatures (650-900 • C).…”
Section: Interdiffusion and Eutectics Under B-dba Conditionsmentioning
confidence: 99%
“…Figure 16. In situ XRD patterns of an E110 alloy with single-layer Cr (a) and multilayer Cr/CrN (b) (layer step-250 nm) coatings under linear heating in the temperature range of 25-1400 • C. Replotted from[195].…”
mentioning
confidence: 99%
“…or Si. Table 2 summarizes the main candidate materials as coatings for nuclear fuel cladding [ 35 , 37 , 47 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Relations Between Microstructures and Alloys Performance Of ...mentioning
confidence: 99%